Assessing Auditory Processing Deficits in Tinnitus and Hearing Impaired Patients with the Auditory Behavior Questionnaire - Diges, Isabel; Simón, Francisco; Cobo, Pedro (Frontiers in Neuroscience, 2017)
Background and purpose: Auditory processing disorders (APD), tinnitus and hearing loss (HL) are typical issues reported by patients in audiologic clinics. These auditory impairments can be concomitant or mutually excluding. APD are not necessarily accompanied by significant HL, whereas many adults exhibit peripheral HL and typical cognitive deficits often associated with APD. Since HL, tinnitus and APD affects to several parts of the ascending auditory pathway from the periphery to the auditory cortex, there could be some interrelationship between them. For instance, tinnitus has been reported to degrade the auditory localization capacity. Tinnitus is believed to be triggered by deafferentation of normal peripheral input to the central auditory system. This peripheral deficit can be accompanied by HL or not, since a type of permanent cochlear damage (thus deafferentation) without an elevation of hearing thresholds might persist. Therefore, a combined study of APD, tinnitus and HL on the same cohort of patients can be audiologically relevant and worthy.